Serial effects of high-resistance and prolonged endurance training on Na+-K+ pump concentration and enzymatic activities in human vastus lateralis - Green, H.; Dahly, A.; Shoemaker, K.; Goreham, C.; Bombardier, E.; Ball-Burnett, L. (Acta Physiologica, 1999)
The purpose of this study was to compare two contrasting training models, namely high-resistance training and prolonged submaximal training on the expression of Na+-K+ ATPase and changes in the potential of pathways involved in energy production in human vastus lateralis. The high-resistance training group (VO2peak = 45.3 ± 1.9 mL kg-1 min-1, mean ± SE, n = 9) performed three sets of six to eight repetitions maximal, each of squats, leg presses and leg extensions, three times per week for 12 weeks, while the prolonged submaximal training group (VO2peak = 44.4 ± 6.6 mL kg-1 min-1, n = 7) cycled 5-6 times per week for 2 h day-1 at 68% VO2peak for 11 weeks. In the HRT group, Na+-K+ ATPase (pmol g-1 wet wt), measured withthe 3H-ouabain binding technique, showed no change from 0 (289 ± 22) to 4 weeks (283 ± 15), increased (P < 0.05) by 16% at 7 weeks and remained stable until 12 weeks (319 ± 19). For prolonged submaximal training, a 22% increase (P < 0.05) was observed from 0 (278 ± 31) until 3 weeks (339 ± 29) with no further changes observed at either 9 weeks (345 ± 25) or 11 weeks (359 ± 34). In contrast to high-resistance training, where a 15% increase (P < 0.05) was observed, only in the maximal activity of phosphorylase, prolonged submaximal training resulted in increases in malate dehydrogenase, b-hydroxyl-CoA dehydrogenase, hexokinase and phosphofructokinase. In contrast to high-resistance training which failed to result in an increase in VO2peak, prolonged submaximal training increased VO2peak by »15%. Only for prolonged exercise training was a relationship observed for VO2peak and Na+-K+-ATPase (r = 0.59; P < 0.05). Correlations between VO2peak and mitochondrial enzyme activities were not significant (P > 0.05) for either training programme. It is concluded that although both training programmes stimulate an up-regulation in Na+-K+ ATPase concentration, only the prolonged submaximal training programme enhances the potential for b-oxidation, oxidative phosphorylation and glucose phosphorylation.